THE PROFILE OF THINKING IN SOLVING ALGEBRA BASED ON SOLO TAXONOMY VIEWED FROM THE LEVEL OF SELF-EFFICACY AT STUDENTS OF SMP AL-AZHAR PALU - Rio Fabrika (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2013)
One factor which determined student’s achievement in learning is self-efficacy which can affect the activities, goals, and efforts that is conducted by students to resolve problem, especially in thinking. Each student has different self-efficacy which will lead them to have different thinking. Therefore, the objective of the research  is to find out the profile of thinking be reveal and classify each tendency of thinking shown by students on four level of thinking based on SOLO (Structure of Observed Learning Outcomes) taxonomy, namely uni-structural, multi-structural, relational, and extended abstract. This is a descriptive research by qualitative approach. This research is as the main instrument which leads by super item test, self-efficacy scale, and a valid interview manual. Subject of the research were students of class VIII-C at SMP Al-Azhar Palu, which consisted of 4 students (2 students in high self-efficacy and 2 students in low self-efficacy. Process of the research were: (a) formulated the thinking indicators based on SOLO taxonomy, (b) formulated a valid and reliable supporting instrument (super item test, self-efficacy scale, and interview manual), (c) took the subject of research based on self-efficacy condition, (d) took data to reveal the thinking level of students by super item test, (e) conducted a triangulation of data analysis, and (h) concluded the result of study. The result revealed that: (a) subject with high efficacy (HE) shows the tendency of thinking on the level of extended abstract, (b) subject with low efficacy (LE) shows the tendency of thinking on the level of relational, (c) subject with the high and low self-efficacy relatively shows a same tendency of thinking on the level of uni-structural, multi-structural, and relational as well as on the extended abstract